Peran Brand Trust dalam Pengaruh Brand Ambassador dan Brand Awareness Terhadap Minat Beli - Wijaya, Andrew Kristya; Suciarto, A.Sentot (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
The purpose of this research is understand the role of brand trust in brand awareness and brand awareness toward purchase intention in the Blibli marketplace.. The background of this research is based on the several research gaps and the phenomenon of the online shopping market that has risen so there are many marketplace players in Indonesia. The research population, namely Gen Z people in Semarang who are interested in try and already using the Blibli marketplace application., This study used non-purposive sampling method which is purposive sampling, sample that used in this study was 100 people. The data was collected by distributing questionnaire in online form by using google form. Data analysis used using the path analysis method the Sobel test to show how much influence the brand trust variable has in mediating the relationship between brand ambassador and brand awareness toward purchase intention with SPSS program. The research results show that Brand Ambassador has positive and significant influence on purchase intention through brand trust and Brand Awareness has positive and significant influence on purchase intention through brand trust.